2012
DOI: 10.1111/j.1467-2979.2012.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and geographic influences on fish otolith microchemistry

Abstract: Fish otoliths are comprised primarily of CaCO3 and grow throughout an individual's lifetime. The chemical composition of otoliths is often a distinctive characteristic of the populations that live in discrete areas, and as a result, it has been used for population classification studies, supporting ecological and fisheries research. However, the deposition of chemical elements in the otolith is influenced by both physiological and environmental factors. We review observed trends in otolith elemental compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 153 publications
(431 reference statements)
5
55
0
1
Order By: Relevance
“…The usefulness of detecting changes in salinity through the analysis of Sr, Ba and Mg in otoliths has been highlighted in general terms, but data interpretation must account for multiple sources of variation including speciesspecificity, temperature and growth effects (reviewed in Campana, 1999;Elsdon et al, 2008;Sturrock et al, 2012;Chang & Geffen, 2013). One concern in the use of otolith geotags to track changes in water characteristics is linked to the effect of physiology in ion incorporation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of detecting changes in salinity through the analysis of Sr, Ba and Mg in otoliths has been highlighted in general terms, but data interpretation must account for multiple sources of variation including speciesspecificity, temperature and growth effects (reviewed in Campana, 1999;Elsdon et al, 2008;Sturrock et al, 2012;Chang & Geffen, 2013). One concern in the use of otolith geotags to track changes in water characteristics is linked to the effect of physiology in ion incorporation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Normalizing the data also had no effect on Authors of other studies have reported significant differences in otolith chemical signatures among species sampled from the same nursery habitats or systems (Gillanders & Kingsford 2003, Hamer & Jenkins 2007, Reis-Santos et al 2008. Typically, co-located species which are more closely related phylogenetically and ecologically tend to have more similar otolith chemical signatures (reviewed in Chang & Geffen 2013). For example, Brown (2006) reported otolith elemental composition was similar between juvenile flatfishes English sole Pleuronectes vetulus and speckled sanddab Citharichthys stigmaeus co-located among 3 regions along the coast of California, and that mean regionspecific LDF classification accuracies differed little when species were modeled separately (78 and 79%, respectively) versus jointly (77%).…”
mentioning
confidence: 99%
“…Otolith chemical signatures have been shown to be effective natural tags in fishes, and examining population connectivity and estimating nursery sources with otolith chemical signatures has become widespread in fish ecology (reviewed in Campana & Thorrold 2001, Elsdon et al 2008, Chang & Geffen 2013. Employing otolith chemical signatures has been particularly effective for examining recruitment dynamics and population connectivity in estuarinedependent and diadromous fishes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations